Quantitative Analysis of Retinal Microvascular Changes in Optical Coherence Tomography Angiography Of Diabetic Retinopathy - Prettyla Yollamanda; Arief Kartasasmita; Iwan Sovani; Erwin Iskandar; Rova Virgana; Grimaldi Ihsan (International Journal of Retina, 2018)
Introduction: Diabetic Retinopathy (DR) is a common microvascular complication in patients with Diabetes Mellitus (DM) that can cause visual impairment and blindness in adult populations. Retinal microvascular changes, reflecting capillary drop out, non perfusion, and retinal ischemia seen in patients with DM can be assessed not only qualitatively, but also quantitatively with the introduction of a new, non invasive imaging modality Optical Coherence Tomography Angiography (OCTA), avoiding potential advese risks that can occur with the use of dye-injection imaging technique. We quantified retinal microvascular changes in healthy control eyes and Diabetic Retinopathy using OCTA. Methods: A cross sectional study included 13 eyes of 9 patients with DR, consists of 11 eyes with Non Proliferative Diabetic Retinopathy (NPDR) and 2 eyes with Proliferative Diabetic Retinopathy (PDR) and 5 eyes of 5 age-matched controls. Participants were imaged with commercial OCTA device (CIRRUS HD-OCT 5000 Angioplex). We analyzed in the Superficial Capillary Plexus (SCP) the following OCTA parameters : Vessel Density (VD), Foveal Avascular Zone (FAZ) area, and FAZ circularity. Result: Normal eyes had a higher mean VD, FAZ circularity (p >0.05) and lower mean FAZ area ( p <0.05) in the SCP compared with the DR (NPDR + PDR) group. If we excluded the PDR eyes from the analytic data, mean VD and FAZ area were found to be lower in control group, and mean FAZ circularity was higher. However, no quantitative parameters were statistically significant between control group and NPDR group. Conclusion: Microvascular changes in DR can be assessed with the use of Optical Coherence Tomography Angioraphy, which is non invasive and provides high quality of images acquired from the chosen level of retina.